Atypical Noncontiguous Multiple Spinal Tuberculosis: A Case Report - Kim, Jang-Hoon (The Korean Spinal Neurosurgery Society, 2014)
OBJECTIVE: Spinal tuberculosis-associated symptoms are not so unique as to immediately indicate the proper diagnosis in most cases. Distinguishing spinal tuberculosis (Pott's disease) from pyogenic spondylitis is often difficult, and lesions metastatic from systemic malignancy are the other major entity from which spinal tuberculosis must be distinguished. CLINICAL PRESENTATION: A 27-year-old male patient presented with a history of back pain after a minor trauma 1 month ago. Computed tomography and magnetic resonance imaging of the thoracic spine showed multiple osteolytic bone lesions at the bodies of T9, T10 and T11 vertebrae and the spinous processes of T12 and L1. Other noncontiguous osteolytic lesions were noted at S2 body and right sacro-iliac joint. INTERVENTION: To confirm the pathologic diagnosis, the patient underwent an open biopsy for the T12 and L1 spinous process lesions and a percutaneous transpedicular biopsy on T9, T10, T11 lesions. Frozen biopsy was reported as compatible with chronic granulomatous caseating necrosis without malignant cells. The final diagnosis was an atypical presentation of multiple spinal tuberculosis. The patient received an appropriate enteral anti-tuberculosis therapy and recovered without any complications. Follow-up MRI taken after a year of medical treatment revealed marked resolution of the lesions. CONCLUSION: Current research indicates the incidence of multi-level noncontiguous, remote vertebral tuberculosis is 1.1% to 16%. Because tuberculous spondylitis could represent variant and atypical pattern, the disease should be considered in differential diagnosis along with other diseases such as metastatic neoplasm, pyogenic spondylitis, especially when the radiologic studies are revealing multiple spinal lesions.